Influência dos desreguladores endócrinos sobre a função tiroidiana e expressão de globinas do sistema nervoso central - Conceicao, Rodrigo Rodrigues da [UNIFESP] (2018)
Endocrine disrupters (EDs) are chemicals or mixtures of chemicals that interfere with any aspect of hormone action, including the regulation of hormone production by affecting the hypothalamic-pituitary-gland axis and genes targeted by these hormones. Human exposure to EDs occurs through ingestion of food and water, inhalation of dust, gases and particulate matter in the air, and also through contact with the skin. The widespread application of silver nanoparticle (AgNPs) and bisphenol A (BPA) in consumer products has inevitably increased human and the environment exposure. In our studies, we decided to investigate whether AgNP and BPA regulate the thyroid axis and if the gene expression of neuroglobin (Ngb) and cytogene (Cygb) could be modulated in the central nervous system (CNS), since both deregulators cross the blood-brain barrier and promote oxidative damage. Wistar rats were submitted to different treatments with AgNP and BPA, and after different periods they were euthanized, so the blood was collected for hormonal dosing. Tissues such as hypothalamus, pituitary, and thyroid were excised for the evaluation of gene expression by the hypothalamic-pituitary-thyroid axis RT-qPCR, and peripheral tissues such as liver, hippocampus, cortex and cerebellum were used to assess peripheral actions. Regarding globins (manuscripts 1 and 2), we found that both AgNPs and BPA promote changes in Ngb and Cygb in the brain and these changes are dose dependent and anatomically specific. Regarding the HPT axis (manuscripts 3 and 4), both deregulators decrease the serum levels of the THs, with a strong influence of the genes directly related to the metabolism, transport and action of the HTs.